Digital technologies and emerging educational objectives: The need for transformational changes in teacher education and training - Garba, Sani Alhaji; Yusuf, Byabazaire (Springer Singapore, 2016)
The institutionalization of information technology in human society has necessitated the emergence of new educational goals and objectives.This study identifies the emerging educational goal and objectives of the twenty-first century and examines the challenging role of higher education in the information age.This article introduces four models that can guide and fast-track the integration of new knowledge domains in the curriculum structure and the development of new instructional and pedagogical designs in higher education to facilitate the attainment of the educational goal and objectives of the twenty-first century. The article also introduces a structural model of providing the foundation needed for higher education in the twenty-first century in the present information and technology-driven world of globalization. Based on existing studies, this article considers the role of teacher education as being critical in addressing the various challenges associated with the transformation changes needed for higher education in the twenty-first century.